Reperfusion Without Functional Independence in Late Presentation of Stroke With Large Vessel Occlusion. Issue 12 (14th October 2022) - Seker, Fatih; Qureshi, Muhammad M.; Möhlenbruch, Markus A.; Nogueira, Raul G.; Abdalkader, Mohamad; Ribo, Marc; Caparros, Francois; Haussen, Diogo C.; Mohammaden, Mahmoud H.; Sheth, Sunil A.; Ortega-Gutierrez, Santiago; Siegler, James E.; et al.
Abstract : Background: Reperfusion without functional independence (RFI) is an undesired outcome following thrombectomy in acute ischemic stroke. The primary objective was to evaluate, in patients presenting with proximal anterior circulation occlusion stroke in the extended time window, whether selection with computed tomography (CT) perfusion or magnetic resonance imaging is associated with RFI, mortality, or symptomatic intracranial hemorrhage (sICH) compared with noncontrast CT selected patients. Methods: The CLEAR study (CT for Late Endovascular Reperfusion) was a multicenter, retrospective cohort study of stroke patients undergoing thrombectomy in the extended time window. Inclusion criteria for this analysis were baseline National Institutes of Health Stroke Scale score ≥6, internal carotid artery, M1 or M2 segment occlusion, prestroke modified Rankin Scale score of 0 to 2, time-last-seen-well to treatment 6 to 24 hours, and successful reperfusion (modified Thrombolysis in Cerebral Infarction 2c–3). Results: Of 2304 patients in the CLEAR study, 715 patients met inclusion criteria. Of these, 364 patients (50.9%) showed RFI (ie, mRS score of 3–6 at 90 days despite successful reperfusion), 37 patients (5.2%) suffered sICH, and 127 patients (17.8%) died within 90 days. Neither imaging selection modality for thrombectomy candidacy (noncontrast CT versus CT perfusion versus magnetic resonance imaging) was associated with RFI, sICH, or mortality. Older age, higher baseline National Institutes of Health Stroke Scale, higher prestroke disability, transfer to a comprehensive stroke center, and a longer interval to puncture were associated with RFI. The presence of M2 occlusion and higher baseline Alberta Stroke Program Early CT Score were inversely associated with RFI. Hypertension was associated with sICH. Conclusions: RFI is a frequent phenomenon in the extended time window. Neither magnetic resonance imaging nor CT perfusion selection for mechanical thrombectomy was associated with RFI, sICH, and mortality compared to noncontrast CT selection alone. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04096248.